2011
DOI: 10.1371/journal.pone.0023260
|View full text |Cite
|
Sign up to set email alerts
|

Host-Size Mediated Trade-Off in a Parasitoid Sclerodermus harmandi

Abstract: Optimality models of host-parasitoid relationships have traditionally assumed that host quality increases as a function of host size at parasitism. However, trade-offs may play a crucial role in species evolution and should be found in host-parasitoid interactions where the host quality may differ between different sizes. Here, we investigated the effects of host size differences of Monochamus alternatus larva on foraging decisions, parasitism and related fitness in a gregarious ectoparasitoid, Sclerodermus ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
5
37
0
1
Order By: Relevance
“…This resulted in browning of the epidermis and sometimes in visible lacunae. Host feeding appeared to promote the longevity of the adult parasitoids and is likely to enhance future fecundity as Sclerodermus are synovigenic anautogenous species (oogenensis takes place after foundress feed on a suitable host) (Liu et al, 2011). In conclusion, this behavior may have some pest control value as S. brevicornis attacks and kills small hosts, even if it does not generate recruits into the next generation of parasitoids.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This resulted in browning of the epidermis and sometimes in visible lacunae. Host feeding appeared to promote the longevity of the adult parasitoids and is likely to enhance future fecundity as Sclerodermus are synovigenic anautogenous species (oogenensis takes place after foundress feed on a suitable host) (Liu et al, 2011). In conclusion, this behavior may have some pest control value as S. brevicornis attacks and kills small hosts, even if it does not generate recruits into the next generation of parasitoids.…”
Section: Discussionmentioning
confidence: 98%
“…In other species in the same genus it was further shown that the occurrence of all-male broods at emergence was related to high developmental mortality and to broods produced by few unmated foundresses (Kapranas et al, 2016b). On the basis of evidence from other Sclerodermus species (Mamaev, 1979;Liu et al, 2011;Tang et al, 2014;Kapranas et al, 2016b), it is likely that S. brevicornis foundresses each lay a small number of male eggs in every clutch and the proportion of all-female broods reflects the probability of those eggs failing to develop to adulthood. We noted that there were no all-female broods produced on ALB hosts and that this host species also yielded the largest S. brevicornis broods, suggesting a low preimaginal mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the outcome depends on host quality, which for parasitoids is associated with the following features of the host: species, shape, size, movement, sound, chemical cues (Vinson, 1976) and age (Colinet et al, 2005). Generally large and young insects are the best hosts for wasps (Da Rocha et al, 2006;Liu et al, 2011). Parasitoids prefer hosts that are the best sources of nutrients for their offspring, and hymenopteran wasps adjust their sex ratios according to host quality in a way that maximizes the benefi ts.…”
Section: Discussionmentioning
confidence: 99%